Correlation between two-dimensional video analysis and subjective assessment in evaluating knee control among elite female team handball players - Stensrud, S.; Myklebust, G.; Kristianslund, E.; Bahr, R.; Krosshaug, T. (British Journal of Sports Medicine, 2011)
Poor frontal plane knee control has been shown to be a risk factor for anterior cruciate ligament injuries in ball/team sports. It is necessary to develop simple tests that can identify players with poor knee control and among other factors be able to optimise preventive training programmes. The present study investigated the correlation between a two-dimensional (2D) video analysis and subjective assessment performed by one physiotherapist in evaluating knee control. We also tested the correlation between three simple clinical tests using both methods. A cohort of 186 female elite team handball players completed three tests: single-leg squat (SLS), single-leg vertical drop jump (SLVDJ) and two-leg vertical drop jump (VDJ). Receiver operating characteristic (ROC) analyses showed good to excellent agreement between 2D video analysis and subjective assessment for SLS and VDJ (area under the ROC curve (AUC) 0.83-0.89), but not for SLVDJ (AUC 0.65-0.76). Poor knee control was detected in 25-40% of the players using SLS and VDJ. In contrast, poor knee control was identified in less than 1% of the subjects based on the SLVDJ test. This indicates that SLVDJ may be inadequate for evaluating poor frontal plane knee control. The correlation between the SLS and VDJ tests was found to be low, suggesting that these tests identified different subjects with poor knee control. These results indicate that subjective assessment can be used to screen for poor knee control and that both SLS and VDJ tests should be used in screening athletes for poor knee control.